Holocene benthic foraminiferal faunas in coastal deposits of the Nakdong River delta (Korea) and Izumo Plain (Japan). (21st January 2016) - Takata, Hiroyuki; Khim, Boo-Keun; Cheong, Daekyo; Shin, Seungwon; Takayasu, Katsumi; Park, Yong-Hee; Lim, Hyoun Soo
Abstract: We documented the Holocene benthic foraminifera in the coastal deposits based on drilled cores ND-01 (Nakdong River delta, southeastern Korea) and HS02 (Izumo Plain, southwestern Japan). The rapid deepening and subsequent gradual shoaling during the Holocene were recognized from the stratigraphic distribution of five clusters (A to E) and the ratio of planktonic foraminifera to the sum of benthic and planktonic foraminifera (P/T ratio) in core ND-01. Comparison of benthic foraminiferal faunas indicated that the faunal composition differs somewhat between the Nakdong River delta and Izumo Plain or Urauchi Bay (the East China Sea). The relationships between MDS axis 1 and the rarefaction and between MDS axis 1 and the RAC kurtosis showed positive and negative linear-like trends, respectively, in both the Nakdong River delta and the Izumo Plain. The biotic response of benthic foraminifera to taxonomic loss also seemed to be common in that both coastal deposits experienced shoaling or enclosing of the bay environments. Despite the different occurrence of benthic foraminifera between the Nakdong River delta and Izumo Plain, transient changes of benthic foraminifera in both areas at ∼8 ka might have been caused by the enhanced influence of the Tsushima Warm Current.